2023
DOI: 10.1021/acs.jafc.3c00347
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Fluorescence Sensor Array Based on Cucurbit[8]uril Complexes Used for the Detection of Multiplex Quaternary Ammonium Pesticides

Abstract: The simultaneous detection of multiple quaternary ammonium pesticides (QAPs) in water is a challenge due to their high solubility in water and similar structures. In this paper, we have developed a quadruple-channel supramolecular fluorescence sensor array for the simultaneous analysis of five QAPs, including paraquat (PQ), diquat (DQ), difenzoquat (DFQ), mepiquat (MQ), and chlormequat (CQ). Not only were QAP samples of different concentrations (10, 50, and 300 μM) in water distinguished with 100% accuracy but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[55][56][57][58] The internal cavities of macrocyclic structures enable the encapsulation of analytes depending on their size and molecular geometries. The favorable recognition abilities of macrocyclic receptors, including cucurbit[n]urils (CB[n]s), [59][60][61] cyclodextrins (CDs), [62][63] calix[n]pyrroles, [64][65] pillar[n]arenes [66] etc., which provide cross-reactive response patterns, have been applied in sensor array applications. Herein, two examples of IDA-driven pattern recognition using off-the-shelf indicators and macrocyclic receptors, including CB[n]s and CDs, are described.…”
Section: Analyte Capture By the Receptor Along With The Release Of Th...mentioning
confidence: 99%
“…[55][56][57][58] The internal cavities of macrocyclic structures enable the encapsulation of analytes depending on their size and molecular geometries. The favorable recognition abilities of macrocyclic receptors, including cucurbit[n]urils (CB[n]s), [59][60][61] cyclodextrins (CDs), [62][63] calix[n]pyrroles, [64][65] pillar[n]arenes [66] etc., which provide cross-reactive response patterns, have been applied in sensor array applications. Herein, two examples of IDA-driven pattern recognition using off-the-shelf indicators and macrocyclic receptors, including CB[n]s and CDs, are described.…”
Section: Analyte Capture By the Receptor Along With The Release Of Th...mentioning
confidence: 99%
“…The examination of the patterns acquired via the use of multivariate algorithms in machine-learning approaches unveils the specific identification and concentration of the substance being analyzed, enabling the concurrent detection of several substances. Array-based sensing has been extensively utilized for quantification and the analysis of several toxic substances such as heavy metal ions, thiols, bacteria, biogenic amines, toxic gases, etc. Particularly, for pesticide quantification, plenty of array sensing elements were utilized based on the catechol dyes–tyrosinase system along with the utilization of push–pull chromophores containing reactive sites (i.e., alcohol, amine, pyridine active groups) and cucurbit[8]­uril complexes for colorimetric and fluorescent discrimination of pesticides, respectively . However, the synthesis of such dyes/receptors faces complicated synthesis along with their sensitivity to different reaction conditions, which limits their practical usage.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] The fluorescent sensor array combines the high selectivity and sensitivity of probes, suitable for multi‐target imaging and analysis. [ 28 ] So it has been widely used in the analysis of complex analytes, including biological macromolecules, cells, and microorganisms. [ 29 ] Recently, Hu et al reported a host–guest sensor array to identify normal cell lines, cancerous cell lines, and cross‐contaminated cells.…”
Section: Introductionmentioning
confidence: 99%